Influence of meteorological elments ![elements] to interdiurnal variability of ragweed (ambrosia) pollen concentrations - Csépe Zoltán; Matyasovszky István; Makra László; Oláh Róbert (2012)
The purpose of the study is to analyze the potential reasons of day-to-day variations of Ambrosia pollen counts for the Szeged region of Southern Hungary in association with meteorological elements. The database includes a ten-year period (1997-2006) comprising the daily ratios of Ambrosia pollen counts (A) (value on the given day per value on the day before) for its pollen season (July 15 - October 16). At the same time, daily values (value on the given day - value on the day before) of 8 meteorological variables (mean temperature, minimum temperature, maximum temperature, temperature range, irradiance, relative humidity, wind speed and rainfall) are considered for the period April 1 - October 31, 1997-2006. When using a novel procedure, factor analysis with special transformation, wind speed, rainfall and temperature range are the most relevant, while minimum temperature and irradiance are the least important meteorological variables influencing daily pollen ratios. Namely, the data set for which A<1.00 can be associated to lower summer temperatures with near-optimum phyto-physiological processes, while the category A>1.00 is involved with high and extreme high temperatures modifying life functions and, hence, interrelationships of the meteorological and pollen variables.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok